2021
DOI: 10.1371/journal.pone.0253630
|View full text |Cite
|
Sign up to set email alerts
|

Presence of atypical genotypes of Toxoplasma gondii isolated from cats in the state of Bahia, Northeast of Brazil

Abstract: In this study, 20 blood, heart, and brain samples were collected from euthanized cats at the Zoonosis Control Centers and Veterinary Clinics in the state of Bahia, Brazil. The sera were examined for anti-T. gondii antibodies using the indirect hemagglutination test. The brains and hearts of seven seropositive cats were ground, and peptide digestion was performed for bioassay in mice. Toxoplasma gondii was isolated in 5/7 (71.42%) of seropositive cats. In these isolates, the parasite was genotyped using the Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Deiró et al [ 28 ] isolated non-archetypal strains of T. gondii from seven naturally infected cats in Bahia, in the Northeast region of Brazil. PCR–RFLP with 11 genetic markers revealed four distinct genotypes.…”
Section: Genotyping Of Non-archetypal Strains Of T Gondiimentioning
confidence: 99%
See 1 more Smart Citation
“…Deiró et al [ 28 ] isolated non-archetypal strains of T. gondii from seven naturally infected cats in Bahia, in the Northeast region of Brazil. PCR–RFLP with 11 genetic markers revealed four distinct genotypes.…”
Section: Genotyping Of Non-archetypal Strains Of T Gondiimentioning
confidence: 99%
“…PCR–RFLP with 11 genetic markers revealed four distinct genotypes. In the genotyping analysis using microsatellite markers, five non-archetypal genotypes were detected in the cats [ 28 ].…”
Section: Genotyping Of Non-archetypal Strains Of T Gondiimentioning
confidence: 99%
“…Toxoplasma gondii exhibits a great genetic variability, which may be associated with different virulence phenotypes. Initially, three clonal archetypes, I, II, and III, were recognized, and these seem to prevail in the US and Europe, but in recent years, so-called nonclonal and variant or recombinant genotypes have been found (Grigg et al 2001; Deiró et al 2021). Those nonclonal genotypes are sometimes associated with more severe clinical disease in humans and animals (de-la-Torre et al 2013; Hamilton et al 2019; Pardini et al 2019; Casartelli-Alves et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…gondii shows high genetic variabilities. Besides the well-known archetypal genotypes I, II and III, a series of studies showed that there are new variant and non-clonal genotypes, which may show different virulence phenotypes (Grigg et al, 2001;Deiró et al, 2021). In Europe, type II is most prevalent not only in animals but also in humans (Fernández-Escobar et al, 2022a); however, non-clonal genotypes might occur, which may be associated with severe clinical outcome (Boothroyd and Grigg, 2002;Elbez-Rubinstein et al, 2009;Pomares et al, 2011).…”
Section: Introductionmentioning
confidence: 99%